Karakterisasi Laju Korosi Baja ST 40 Berlapis Polyester Putty Dalam Lingkungan Air Payau - Muhammad Jamaluddin Anwar; Edi Widodo (Universitas Muhammadiyah Sidoarjo, 2017)
The attack caused damage of corrosion (rust) is the general problem that causes the degradation of the material as the interaction with the environment and shorten the lifetime of material. Steel ST 40 is a common material used in the industrial, shipping, engineering products, home wares and others. Prevent the occurrence of direct contact with the outside environment by using a coating of polyester putty, serves to prevent the occurrence of oxidation reactions of the nature of corrosion. Coating using polyester putty give influence on the material test of resistance to corrosion. The missing mass on the specimen using a coating of polyester putty of mass loss reached 2,090 mg. whereas in the specimen undergoes the smallest mass loss of 1,090 mg. Whereas in the material without upholstery polyester putty of mass lost most of the specimens that do not use coating polyester putty with the missing mass reach 4,390 mg. Whereas in the specimen menggalami the smallest mass loss of 3,560 mg. On the specimen that is experiencing the highest rate of corrosion occurred in unpublished material using polyester putty of 26.11 Mpy whereas the smallest lajukorosi reached 21.52 Mpy. While the biggest missing mass on a material without polyester putty of 0.98 Mpy, the rate of corrosion of the smallest reach 0.56 Mpy.